A study to evaluate mobile phone dependence among students of a medical teaching institute in Mumbai - Sodhani, Shreya; Gupta, Priyanka; Shah, Anuradha Kunal (International Journal Of Community Medicine And Public Health, 2020)
Background: Mobile phone use has become such a significant part of the life of medical students that they do not realize their level of dependence on their cell phones. It is therefore imperative to identify the threshold where mobile phones cross the line from being a helpful tool to becoming one that enslaves the users. They need to be made aware of the harmful effects of excessive use of mobile phones and counseled about ways to avoid it. This study aims to assess the prevalence and pattern of mobile phone dependence among medical students. Methods: A cross sectional study was conducted among MBBS students of a medical teaching institute in Mumbai. A predesigned and pretested questionnaire (NMP-Q) was sent to all the students out of which 205 students responded and consented to participate in the study. Results: Amongst all the study participants, 47.3% were males (97/205) and 52.7% were females (108/205). Mild Nomophobia was found in 19.04% students whereas 50.70% had moderate and 30.26% had severe Nomophobia. Amongst the males, 56.7% and 26.8% had moderate and severe Nomophobia, respectively while in females, moderate and severe Nomophobia was found to be 45.4% and 33.3%, respectively. Conclusions: Mobile phone dependence is prevalent amongst medical students.